2014
DOI: 10.1353/rhe.2014.0011
|View full text |Cite
|
Sign up to set email alerts
|

College on Credit: A Multilevel Analysis of Student Loan Default

Abstract: This study updates and expands the literature on student loan default. By applying multilevel regression to the Beginning Postsecondary Students survey, four key findings emerge. First, attending proprietary institutions is strongly associated with default, even after accounting for students’ socioeconomic and academic backgrounds. Second, cumulative loan debt has a non-linear relationship to defaulting. Third, minoritized and students from low-income families default at disproportionately high rates; and four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
93
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 39 publications
3
93
0
Order By: Relevance
“…Society also pays when completion rates are low. Taxpayers, who provide the majority of funding for community colleges, subsidize seats in classes for students who never earn the credentials needed to power the state's workforce, and students who do not complete degrees are much more likely to default on their student loans than students who graduate (Hillman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Society also pays when completion rates are low. Taxpayers, who provide the majority of funding for community colleges, subsidize seats in classes for students who never earn the credentials needed to power the state's workforce, and students who do not complete degrees are much more likely to default on their student loans than students who graduate (Hillman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Steiner and Teszler () estimated that students who graduated from college had a 2% chance of default, while those who did not graduate had a 14% likelihood of default. Hillman () reviewed factors associated with student loan default and found that the primary factors were demographics (race, age, and gender), socioeconomic factors, academic experiences, postcollege employment, and institutional characteristics.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The strand of this literature which deals with default rates is the most relevant to the current study. Dynarski (1994) and Hillman (2014) examine the characteristics which correlate with eventual default on their loans, nding unsurprisingly that borrowers from low-income households, college dropouts, and those with the lowest post-college earnings were the most likely to default on their student loans. Ionescu (2009) tests the impact of various student loan policies (e.g.…”
Section: Previous Literaturementioning
confidence: 99%